INFLUENCE OF TEACHING RESOURCES ON DEAF STUDENTS’ ACADEMIC PERFORMANCE IN SCIENCES AT NGALA SCHOOL FOR THE DEAF, NAKURU COUNTY, KENYA - Okeng’o, Geoffrey Mienda; Kikwai, Caren (IJRDO- Journal of Educational Research, 2020)
The study sought to determine the influence of teaching resources on deaf students’ academic performance in sciences at Ngala School for the Deaf, Nakuru County, Kenya.  The study used a descriptive case study design. The target population is 472 respondents at Ngala secondary school of the deaf. Quantitative data was presented using percentages, frequency tables and charts. The study found out that the laboratory remained the most utilized resource in school. Although there were variety charts, computers most of them remained underutilized in the learning of science subjects. Some teachers lacked essential skills in operating the computer hence could not exploit them in science learning. The study concluded that the teachers are not adequately utilizing computer or internet, charts, and videos in science class which were some of the methods that could enhance online learning, a modern approach to 21st century learning. This lack of resources utilization had affected the learners’ motivation and overall understanding of science concepts in class.  The study recommended that the Ministry of Education Sciences and Technology should intensify SMASSE inset to train teachers on how to use and improvise the limited available resources in classroom.